Cross-linking of rubber in the presence of multi-functional cross-linking aids via thermoreversible Diels-Alder chemistry. (September 2016) - Polgar, L.M.; Fortunato, G.; Araya-Hermosilla, R.; van Duin, M.; Pucci, A.; Picchioni, F.
Graphical Abstract: Highlights: Two components (a rubber and a thermoset) are mixed and thermoreversibly cross-linked by using Diels-Alder chemistry. Cross-link densities are increased beyond the limit imposed by the degree of functionalization. Multi-functionalized oligomer acts a as cross-linking aid for the rubber matrix and, as such, results in different network topologies (and in turn different properties). Abstract: Furan-functionalized polyketone (PK-FU) was added to a furan-functionalized ethylene-propylene rubber (EPM-FU). The mixture was subsequently cross-linked with a bismaleimide through Diels-Alder chemistry in order to improve the mechanical properties of the rubber. Infrared spectroscopy showed the reversible interaction between both polymers and the bismaleimide cross-linker. Likewise, mechanical measurements indicated the re-workability of the mixtures with no evident differences in storage modulus and mechanical properties after several heating cycles. The cross-link density and mechanical properties, such as hardness, tensile properties and compression set, could be modulated by changing the degree of furan functionalization of PK-FU and the PK-FU loading in the blends. It is concluded that PK-FU has some characteristics of an inert filler, but mainly acts as a multi-functional cross-linking aid, enabling larger amounts of bismaleimide to cross-link EPM-FU.